Theorien und Praktiken der Autorschaft - Schaffrick, Matthias; Willand, Marcus (Spectrum Literaturwissenschaft, 2014)
Since the "return of the author," questions of literary and scientific authorship have been garnering more attention. This volume clearly presents the research literature in this field, and describes theories and practices of authorship through historical and systematic case studies from the perspectives of hermeneutics, poststructuralism, narratology, fiction theory, genre studies, and staging strategies
Literaturangaben
Keywords: Konferenzschrift -- 2011 -- Berlin; Geschichte; Selbstdarstellung; Autor; Autorschaft